DIGITAL ECONOMY AS A FACTOR OF SUSTAINABLE DEVELOPMENT GOALS PROGRESSION IN KAZAKHSTAN - Dauliyeva, G.; Islamoglu, M.; Yeraliyeva, A. (Farabi Journal of Social Sciences, 2023)
Currently, there has been a growing global concern regarding sustainable development, environmental impact, economic inequality, and social inequality among countries and various demographic segments. The international community, including the United Nations and other political and economic alliances, is actively engaged in endeavors to advance the Sustainable Development Goals, aimed at solving these issues at the global and national level. Kazakhstan has also taken a number of measures and initiatives to achieve the abovementioned goals for a secure, equal, and progressive shared future. This study aims to examine the role of the digital economy as a tool for the effective implementation of designated goals. It shows the correlation between Sustainability and Global competitiveness and analyzes current trends and key elements of the digital economy in Kazakhstan that contribute to the realization of sustainable development objectives. The study has been carried out using qualitative content analysis and an extensive examination of existing literature. The article concludes by offering recommendations to enhance the effectiveness of the digital economy in Kazakhstan as a driver of Sustainable Development Goals achievement. Keywords: sustainable development, digital economy, digitalization, SDG